2019
DOI: 10.1017/s1743921319007981
|View full text |Cite
|
Sign up to set email alerts
|

X-ray sources in Galactic globular clusters and old open clusters

Abstract: The features and make up of the population of X-ray sources in Galactic star clusters reflect the properties of the underlying stellar environment. Cluster age, mass, stellar encounter rate, binary frequency, metallicity, and maybe other properties as well, determine to what extent we can expect a contribution to the cluster X-ray emission from low-mass X-ray binaries, millisecond pulsars, cataclysmic variables, and magnetically active binaries. Sensitive X-ray observations with XMM-Newton and certainly Chandr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Verbunt & Hut (1987 [105]) showed that bright X-ray sources in GCs seem consistent with being formed through dynamical interactions. There are currently 21 bright X-ray sources in 15 GCs, being eight persistent and 13 transients (van den Berg 2020 [68]), and they are still consistent with being dynamically formed, especially considering their mass density, which is much higher than in the Galactic disc. Pooley et al (2003 [106]) analysed Chandra observations of 12 GCs and found that the number of X-ray sources correlates with Γ.…”
Section: Pos(golden2019)013mentioning
confidence: 99%
See 2 more Smart Citations
“…Verbunt & Hut (1987 [105]) showed that bright X-ray sources in GCs seem consistent with being formed through dynamical interactions. There are currently 21 bright X-ray sources in 15 GCs, being eight persistent and 13 transients (van den Berg 2020 [68]), and they are still consistent with being dynamically formed, especially considering their mass density, which is much higher than in the Galactic disc. Pooley et al (2003 [106]) analysed Chandra observations of 12 GCs and found that the number of X-ray sources correlates with Γ.…”
Section: Pos(golden2019)013mentioning
confidence: 99%
“…Finally, they could also be detected as X-ray sources, which is generated in the boundary layer (in case of DNe) or in the post-shock region (in case of magnetic CVs) (see e.g. van den Berg 2020 [68] and references therein).…”
Section: Searches For Cataclysmic Variables In Globular Clustersmentioning
confidence: 99%
See 1 more Smart Citation